Prediction of Financial Distress With Financial Ratio Analysis - Abdul Rahman; Deliana Deliana; Riswanto Riswanto; Raya Puspita Sari Hasibuan (Universitas Islam Bandung, 2022)
This study aims to prove the effect of liquidity, profitability and leverage on financial distress. The study was conducted in mining companies listed on the Indonesia Stock Exchange. The population of this study was the financial statements of mining companies listed on the Indonesia Stock Exchange in 2014-2019. The sample was determined using purposive sampling using certain criteria. The test was carried out using multiple regression analysis with SPSS software assistance. The results of this study indicate that the liquidity variable has no effect on financial distress, while profitability and leverage have an effect on financial distress.